MANAJERIAL KEPALA MADRASAH DALAM MENCIPTAKAN MADRASAH EFEKTIF DI MA AL FATAH KEC NATAR KAB LAMPUNG - Dwiki Al Akhyar (UNISAN JURNAL, 2024)
The managerial ability of the Madrasah principal is an important and strategic factor in the framework of improving the quality and progress of the Madrasah he leads. The formulation of the problem in this study is how to plan (planning) the Madrasah Head in creating an effective Madrasah at MTs Al Ma’arif, Bumi Pratama Mandira District, Sungai Menang District. Ogan Komering Ilir South Sumatra? The purpose of this study was to describe the managerial head of Madrasah regarding planning, organizing, directing and controlling so as to create an effective Madrasa. This study used descriptive qualitative methods. The data sources of this research are the head of Madrasah (as key informant), deputy head of Madrasah, and teachers. Data collection techniques through observation, interviews, and documentation. Conclusion The results of the study are: 1) Planning (planning Madrasah heads in creating effective Madrasahs in accordance with the criteria for effective Madrasas., 2) Organizing Madrasah heads in creating effective Madrasahs according to procedures., 3) Directing (directing Madrasah heads in creating effective Madrasas). has also been going well., 4) Controlling is carried out by the head of Madrasah in creating effective Madrasahs by monitoring and evaluating. From the overall managerial head of Madrasah, it can be stated that the head of MA Al Fatah Natar has been able to create an effective Madrasah because it has implemented effective Madrasa indicators that refer to the input, process, output and outcome of Madrasahs. . Keywords: Managerial, Madrasah, Effective